Dabrafenib and trametinib therapy in an elderly patient with non‐small cell lung cancer harboring the BRAF V600E mutation. Issue 2 (20th November 2020) - Dotsu, Yosuke; Fukuda, Minoru; Honda, Noritaka; Gyotoku, Hiroshi; Kohno, Yoshihisa; Suyama, Takayuki; Umeyama, Yasuhiro; Taniguchi, Hirokazu; Takemoto, Shinnosuke; Yamaguchi, Hiroyuki; Miyazaki, Taiga; Sakamoto, Noriho; et al.
Abstract: Dabrafenib and trametinib therapy for BRAF V600E‐mutant non‐small cell lung cancer (NSCLC) has demonstrated strong antitumor effects in clinical trials and has been approved for use in clinical practice. However, the efficacy and safety of this combination therapy in elderly patients remain unclear. An 86‐year‐old male patient, who had been diagnosed with lung adenocarcinoma with the BRAF V600E mutation, received dabrafenib and trametinib combination chemotherapy. The tumor shrunk rapidly; however, therapy was discontinued after 40 days because adverse events (hypoalbuminemia, peripheral edema, and pneumonia) developed. Although this targeted combination therapy seemed to cause relatively severe adverse events compared with single‐agent targeted therapy in this "oldest old" elderly patient, the marked tumor shrinkage prolonged the patient's life and helped him to maintain a good general condition. Active targeted therapy may therefore be considered with appropriate drug dose reduction instead of conservative treatment, even if a patient is extremely old. Abstract : An 86‐year‐old male patient, who had been diagnosed with lung adenocarcinoma with BRAF V600E mutation, received dabrafenib and trametinib combination chemotherapy. The tumor shrunk rapidly; however, therapy was discontinued after 40 days because adverse events (hypoalbuminemia, peripheral edema, and pneumonia) developed. Although this targeted combination therapy seemed to cause relatively severe adverse events compared with single‐agent targeted therapy in this "oldest old" elderly patient, the marked tumor shrinkage prolonged the patient's life and helped him to maintain a good general condition.